Different Is There a Difference in The Level of Disclosure of Sustainability Reports of Participants and Non-Participants of Asia Sustainbility Reporting Rating (ASRRAT)? - Syefira Ramadhani; Kurnia Ekasari; Hesti Wahyuni (PT. EQUATOR SINAR AKADEMIA, 2023)
A quality sustainability report can reflect that a company is committed to the surrounding environmental, social and economic issues. The National Center for Sustainability Reporting (NCSR) initiated the Asia Sustainability Reporting Rating (ASRR) which aims to motivate and accelerate corporate sustainability reporting by rewarding outstanding efforts to communicate the company's performance in three aspects (economic, social and environmental). The purpose of this study is to study and compare the level of completeness of GRI standard disclosures in the company's Sustainability Report in the banking sub-sector between participants who enter the ASRRAT and not to be participants. The type of research used is qualitative research with a descriptive analysis method of primary data on 6 company Sustainability Reports included in the banking sub-sector. From the 6 banking companies, it can be concluded that ASRRAT participating companies have a higher GRI disclosure commitment than non-ASRRAT participants. This shows that the level of concern from ASRRAT participating companies, to the community and stakeholders has increased in terms of sustainability reporting. So it can be concluded that the completeness of the GRI disclosure is not the only factor that the report falls into the category of ASRRAT participants. It could be that the quality and consistency of sustainability report disclosures are other factors that the company was selected as a member of ASRRAT.